Estrogen-dependent MicroRNA-504 Expression and Related Baroreflex Afferent Neuroexcitation via Negative Regulation on KCNMB4 and KCa1.1 β4-subunit Expression. (21st August 2020) - Feng, Yan; Liu, Yaoyao; Cao, Pan-Xiang; Sun, Xun; Li, Ke-Xin; Li, Xin-Yu; Liu, Li; Wang, Hong-Dan; Cui, Chang-Peng; Xiong, Xue; Zhang, Hao-Cheng; Qiao, Guo-Fen; et al.
Graphical abstract: When female rats (OVI) reach the post-menopausal age (OVX), the neuronal excitability of female-specific subpopulation of myelinated Ah-type baroreceptor neurons is significantly reduced due presumably to the down-regulation of microRNA-504 (miR-504) in the absence of estrogen. This down-regulated miR-504 then leads inversed up-regulations of KCNMB4 gene and its protein KCa1.1 β4-subunit because of conservative binding profiles between miR-504 and KCNMB4, which eventually causes the reduced neuroexcitation of baroreflex afferent pathway and increased blood pressure (BP). Highlights: KCa1.1-β4 subunits express lower level in female vs. male rats in the NG & NTS. Reduced excitability of Ah-types is restored by paxilline & iberiotoxin further. Bioinformatic data show conservative binding profiles between KCNMB4 and miR-504. miR-504 negatively regulates KCa1.1-β4 subunit expression in BRx afferent pathway. KCa1.1-β4/miR-504 expressed in Ah-types is the key for sex-dimorphic excitation. Abstract: Large conductance of Ca 2+ -activated K + channel (KCa1.1) plays an inhibitory role in neuroexcitation. However, the expression of KCNMB4/β4-subunit in the nodose ganglia (NG) and nucleus tractus solitarius (NTS), and its effect and regulation on baroreflex afferent function at post-transcriptional level of female rats remains unknown. Here, we demonstrated that the expression of β4-subunit encoded by KCNMB4 was significantly lower in females vs. males and ovariectomized (OVX) rats in the NG. Although all baroreceptor neurons (BRNs) expressed β4-subunit, altered discharge characteristics were only observed in Ah-type neurons after ovariectomy. Notably, the decreased excitability of Ah-types was restored by paxilline and further enhanced by iberiotoxin. The consistent changes were observed in excitatory post-synaptic currents. The level of miR-504 was higher in females, which was predicted to bind to the 3′UTR of KCNMB4. In consistent, an inverse expression pattern between miR-504 and KCNMB4 was observed in baroreflex afferents. The paxilline-sensitive β4-subunits is less in Ah-types and up-regulated by ovariectomy. These data indicated that KCa1.1 β4-subunit is the key regulator in neuroexcitation of Ah-types and sexual-dimorphism in baroreflex afferent function through estrogen-dependent inhibition of KCNMB4 expression via miR-504.